Role of Pb Doping on the Thermoelectric Properties of Mg3Sb1.8‐yBi0.2Pby Alloys. Issue 12 (8th November 2022) - Zhu, Bo; Lu, Xu; Hu, Lianglu; Zhang, Qiang; Wang, Lifei; Zheng, Yun; Fan, Jianfeng
Abstract: In this work, we focused on the matrix material with a composition of Mg3 Sb1.8 Bi0.2 . The effect of Pb doping on the thermoelectric properties of Mg3 Sb1.8‐y Bi0.2 Pby (y=0, 0.005, 0.01, 0.02) compounds was investigated. Mechanical alloying followed by spark plasma sintering was employed to synthesize the corresponding bulk materials. The x‐ray diffraction results indicate that the doping limit of Pb in Mg3 Sb1.8 Bi0.2 is 0.01∼0.02. Pb doping significantly increases the carrier concentration up to >10 19  cm −3, while decreasing the Seebeck coefficient. Moreover, the thermal conductivity of the matrix material is reduced upon Pb doping at 400–700 K. As a result, the thermoelectric figure of merit is improved in the low‐temperature range, and a ZT value of 0.039 is obtained for the y=0.005 sample at 500 K, which is 77% higher than that of the undoped sample. Abstract : The influence of Pb doping on the thermoelectric properties of Mg3 Sb1.8‐y Bi0.2 Pby was investigated. Pb doping (y=0.01) results in increased hole concentration, reduced thermal conductivity, and enhanced average ZT value over a wide temperature range.